Prevalence of the third canal in the mesial root of the first permanent mandibular mollars, in patients attended in Serodu Clinic, Ecuador - Chávez-Vega, Alex (2018)
Aim: To determine the prevalence of three canals in the mesial root of the first permanent mandibular molars, of patients who come for root canal treatment at the dental clinic of the Equinoctial Technological University, Quito, Ecuador from January 2013 to December 2017. Materiales and Methods : A descriptive observational study is presented, in a sample of 55 clinical histories of patients with root canal treatment at the dental clinic of the Health Sciences faculty "Eugenio Espejo" of the Equinoctial Technological University, between January 2013 to December 2017. After a review of the medical records of patients treated during this period of time and inclusion criteria, the selected radiographs were examined in a negatoscope with the help of a magnifying glass, by a single person trained in reading images and with experience in endodontic treatments. The findings were reported in specially developed Excel tables, for later statistical analysis, through the SPSS program.